Poder de controle no fundo de investimento - Kugler, Herbert Morgenstern (2021)
This thesis deals with the power of control in the scope of the investment fund. It seeks to identify who is the holder of the control power in the investment fund, by analyzing its legal nature according to the current rules. Once the investment fund is located in the Brazilian system and based on its legal nature, it started to remember the elements of the power of control, mainly in the scope of Corporate Law, as well as in other associative forms of Civil Law, such as the condominium, the association and the foundation. Armed with such instruments, we address the holder of the controlling power in the investment fund and its main facets